Thermal, structural and morphological characterization of dental polymers for clinical applications - Benli, Merve; Gumus, Beril Eker; Kahraman, Yusuf; Yagci, Ozlem; Erdogan, Duygu; Huck, Olivier; Ozcan, Mutlu (JAPAN PROSTHODONTIC SOC, 2021)
Purpose: Polymers are used in dentistry on a daily basis due to their mechanical, functional and aesthetic properties. However, such biomaterials are subject to deterioration in the oral environment. Thus, this study aimed to evaluate the structural properties of live commonly used dental polymers to determine their best clinical indications. Methods: Four hundred-fitly samples of five dental polymers (polyethylenterephthalat - glycol modified (PG), polymethyl methacrylate (PA), ethylene vinyl acetate(E), polycarbonate (PC), polyetheretherketone (PK) were prepared to investigate their thermal, structural and chemical characteristics using energy dispersive spectroscopy (EDS), Fourier transform infrared analysis(FTIR), scanning electron microscopy (SEM), differential scanning calorimetry(DSC), thermogravimetric analysis(TGA), X-ray difTraction(XRD), and Shore D hardness test. Data were analyzed using one-way ANOVA, Tukey's HSD, and Levene's tests (alpha=0.05). Results: PK (87.2) and PA (82.4) displayed the highest hardness values and smooth surfaces, as observed with SEM (p<0.001). Silica was detected in PK, PA. and E by EDS and XRD. The highest glass transition temperature was recorded for PC (145.00 +/- 2.00 degrees C) and PK (143.00 +/- 1.87 degrees C), while the lowest value was measured for E (50.00 +/- 2.12 degrees C)(p<0.001). The highest mass loss was detected for PG (91.40 +/- 1.40%) by TGA. Conclusions: PA and PK polymers can be used for stress-containing treatments due to their mechanical properties. These two materials are also advantageous in terms of plaque accumulation as these polymers reveal smoother surfaces than other groups. Insufficient physical and thermal properties require the use of F with caution and only in limited clinical indications.
Keywords: Dental Polymer; FTIR; Hardness; Thermal Stability; TGA; XRD; MECHANICAL-PROPERTIES; ELECTRICAL-PROPERTIES; SURFACE-ROUGHNESS; RESIN COMPOSITES; GRAPHENE OXIDE; POLYETHERETHERKETONE; STABILITY; FIBER; PEEK; Dentistry, Oral Surgery & Medicine